Osmanlı komşuluk hukuku - Kılıç, Seval (My University, 2022)
Komşuluk, insanların sosyal ilişkileri bakımından aileden sonra gelen ilk basamaktır. İnsanların birbirine ihtiyaç duyması, onları bir arada yaşamaya teşvik eder. Bir arada yaşama kuralları da komşuluk hukukunu meydana getirmektedir. Bu çalışmada dar ve geniş kapsamıyla Osmanlı komşuluk hukuku ele alınmıştır. komşuluk hukukuna ilişkin temel kavramların tespit edilip açıklanmasına ayrılmıştır. Komşuluğun yanında hem içerik hem de fiziksel bakımdan daha geniş bir kavram olan “mahalle” üzerinde de durulmuştur. Bu iki temel hususların dışında şehir, semt, köy kavramlarından da kısaca bahsedilmiştir. İkinci bölümde mülkiyet haklarının kısıtlanması bakımından komşuluk hukuku üzerinde durulmuştur. Özellikle zarar-ı fahiş ve komşunun şuf’a hakkı etraflıca izah edilmiştir. Komşuların birbirine fahiş zarar verecek şekilde eylemlerde bulunmasının bütün hukuk sistemlerinde hukuka aykırı olarak tanımlandığından bahsedilmiştir. Üçüncü bölüm, komşuların mahalleli sıfatıyla yüklendiği sorumluluklar ve bu sorumlulukları ne şekilde yerine getirdikleri, bireyler ile mahalleli arasındaki hukuki ilişkilerden oluşmuştur. Vakıfların kamu hizmetlerinin görülmesindeki rölü, şahsa kefalet, kasame ve bir suçtan dolayı toplu sorumluluk, mahalleden ihraç bu bölümün önemli başlıkları arasındadır. Çalışmanın son bölümünde komşuluk hukukunun Tanzimat döneminde ne şekilde değişikliğe uğradığı incelenmiştir. Kadının yetkilerinin azaltılması, bu yetkilerin çeşitli nazırlıklara verilmesi, Yeniçeri ocağının kaldırılması, muhtarlıkların ve belediyelerin kurulması, ebniye nizamnamelerinin birbirine komşu olan evlerin fiziki yapısına etkisi bu bölümde araştırılmıştır.

Neighborhood is the first step after the family in terms of people's social relations. People's need for each other encourages them to live together. The rules of coexistence also constitute the law of neighborhood. In this study, Ottoman neighborhood law has been discussed with its narrow and wide scope. The first chapter is devoted to identifying and explaining the basic concepts of neighborhood law. In addition to the neighborhood, the mahalle, which is a broader concept in terms of both content and physicality in Turkish, is also emphasized. Apart from these two basic issues, the concepts of city, district and village are also briefly mentioned. In the second part, neighborhood law is emphasized in terms of restriction of property rights. Especially the excessive harm and the neighbor's right to preemption have been explained in detail. It has been mentioned that the actions of neighbors that cause excessive harm to each other are defined as unlawful in all legal systems. The third part consists of the responsibilities of neighbors as residents of the neighborhood and how they fulfill these responsibilities, and the legal relations between individuals and residents of the neighborhood. The role of foundations in the performance of public services, personal surety, kasame and collective responsibility for a crime, expulsion from the neighborhood are among the important topics of this section. In the last part of the study, how the neighborhood law changed during the Tanzimat period was examined. The reduction of Qadi's powers, the assignment of these powers to various ministries, the abolition of the Janissary corps, the establishment of mukhtars and municipalities, the effects of building regulations on the physical structure of neighboring houses have been examined in this section.
Keywords: History; Hukuk; Kamu hukuku; Komşuluk; Law; Neighborhood; Public law; Tarih; tarih law; Turkey; Türkiye